Toward sustainable solid polymer electrolytes for lithium-ion batteries - Barbosa, João C. (2022)
Lithium-ion batteries (LIBs) are the most widely used energy storage system due to their high energy density and power, robustness and reversibility, but they typically include an electrolyte solution constituted of flammable organic solvents, leading to safety risks and reliability concerns for high energy density batteries. A step forward in Li-ion technology is the development of solid-state batteries suitable in terms of energy density and safety, for a next generation of smart, safe and high-performance batteries. Solid-state batteries can be developed based on a solid polymeric electrolyte (SPE) that may rely on natural polymers in order to replace synthetic ones to take into account environmental concerns. This work provides a perspective on the current state-of-the-art of sustainable SPEs for lithium-ion batteries. The recent developments are presented with a focus on natural polymers and their relevant properties in the context of battery applications. In addition, the ionic conductivity values and battery performance of natural polymer based SPEs are reported and it is shown that sustainable SPEs can become essential components of a next generation of high-performance solid-state batteries synergistically focusing on performance, sustainability and circular economy considerations